Exercise and Fall Prevention: Narrowing the Research‐to‐Practice Gap and Enhancing Integration of Clinical and Community Practice. Issue 2 (30th January 2016) - Li, Fuzhong; Eckstrom, Elizabeth; Harmer, Peter; Fitzgerald, Kathleen; Voit, Jan; Cameron, Kathleen A.
Abstract : Falls in older adults are a global public health crisis, but mounting evidence from randomized controlled trials shows that falls can be reduced through exercise. Public health authorities and healthcare professionals endorse the use of evidence‐based, exercise‐focused fall interventions, but there are major obstacles to translating and disseminating research findings into healthcare practice, including lack of evidence of the transferability of efficacy trial results to clinical and community settings, insufficient local expertise to roll out community exercise programs, and inadequate infrastructure to integrate evidence‐based programs into clinical and community practice. The practical solutions highlighted in this article can be used to address these evidence‐to‐practice challenges. Falls and their associated healthcare costs can be reduced by better integrating research on exercise intervention into clinical practice and community programs.